2020
DOI: 10.1039/d0mt00054j
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(iii) complexes containing thiazole-based ligands that modulate amyloid-β aggregation

Abstract: Alzheimer's Disease (AD) is a devastating neurodegenerative disorder where one of the commonly observed pathological hallmarks is extracellular deposits of the peptide amyloid-β (Aβ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 77 publications
3
22
0
Order By: Relevance
“…Electrospray ionization-mass spectrometry (ESI-MS) analysis, evidenced the formation of adducts formed upon reaction of the compound with the peptide and thioflavin T assay, revealed that the presence of the Ru complex greatly reduces peptide aggregation in vitro [ 15 ]. Derivatives of NAMI-A and PMRU20 exhibit enhanced affinity toward Aβ 1–40 [ 16 ]. The complex fac -[Ru(CO) 3 Cl 2 (N 1 -thz)] (thz = 1,3-thiazole) binds the 1–28 fragment of the β−amyloid peptide [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization-mass spectrometry (ESI-MS) analysis, evidenced the formation of adducts formed upon reaction of the compound with the peptide and thioflavin T assay, revealed that the presence of the Ru complex greatly reduces peptide aggregation in vitro [ 15 ]. Derivatives of NAMI-A and PMRU20 exhibit enhanced affinity toward Aβ 1–40 [ 16 ]. The complex fac -[Ru(CO) 3 Cl 2 (N 1 -thz)] (thz = 1,3-thiazole) binds the 1–28 fragment of the β−amyloid peptide [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…31 Although all three complexes were found to impact the aggregation and toxicity of Aβ, PMRU20 emerged as a lead candidate. The subsequent preparation and evaluation of several azole-based derivatives of both NAMI-A and PMRU20 (Figure 1) 32,33 confirmed the importance of hydrogen bonding in coordinating and subsequently minimizing the aggregation of the peptide. Additionally, symmetry around the metal center was not a determining factor for activity, but rather the azole ligand itself governed the performance of the complex.…”
Section: ■ Introductionmentioning
confidence: 88%
“…This observation reflects previous studies of azole-containing Ru complexes, where the amino functional group was essential for activity. 32 By contrast, all remaining complexes had substantially lower absorbance readings relative to Ru-P9, with Ru-P8 having the next highest absorbance. Both Ru-P9 and Ru-P8 have terminal primary amines at the apical position on the pyridine ligand, suggesting that N−H hydrogen bonding with Aβ is responsible for their activity.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This suggests that these compounds may not be as hazardous to mammalian cells. Short term incubation, with other compounds, has been shown previously to elicit acute cytotoxicity in glial cells [96]. A therapeutic use of these compounds targeted toward inhibiting Leishmania based infection should be further investigated.…”
Section: Detection Of Leishmania Nitric Oxide Using a Specific Fluorementioning
confidence: 98%